Air Quality, Atmospheric Variables and Spread of COVID-19 in Delhi (India): An Analysis - Abhishek Dutta; Wanida Jinsart (Aerosol and Air Quality Research)
Abstract Based on a time series analysis of the criteria pollutants, meteorological parameters, and COVID-19 positive cases, this paper explores the impact of epidemic prevention and control actions on air quality for five different periods of COVID-19 outbreak in Delhi, India. The study found that under the epidemic control measure during 11 May–19 June 2020, the average concentrations of atmospheric air pollutants PM2.5, PM10, NO2, and CO were reduced to 42.15 µg m–3, 128.68 µg m–3, 27.31 ppb, and 0.83 ppm respectively, and were 73.85%, 46.48%, 63.43%, and 50.18% lower than the pre-COVID-19 level of January 2020, respectively. The steep fall of PM2.5, NO2, and CO was due to a drastic reduction in vehicular emission, but PM10 did not fall below the National Ambient Air Quality Standard. Between January 2020 to 11 May–19 June 2020 period, the pollutants O3 and SO2 increased significantly by 217.33% and 57.58 % respectively. The rise of SO2 in Delhi was due to long-distance transfer, power plant emissions, and biomass burning. The sharp increase of O3 happened due to accumulation in the atmosphere. During the peak COVID-19 phase (9 April–10 May 2020) Delhi had unprecedented improved AQI classes of II and III only. However, the pivotal pollutants in terms of their cumulative contribution to the AQI classes were PM10 and O3. Low RH and low-temperature situations exhibited positive correlations with the new COVID-19 infection cases in Delhi. Comparatively lower NO2 level in the air demonstrated a significant negative correlation with new COVID-19 cases while average SO2 concentration in the air, when increased to 24.05 ppb, showed a negative correlation with new COVID-19 cases in Delhi. This study indicated a possibility of O3 exhibiting a positive correlation with new COVID-19 cases under the condition of comparatively low temperature and low humidity.